Early and long-term prognosis in patients with remaining chronic total occlusions after revascularization attempt. A cohort study from the SKEJ-CTO registry. (1st January 2023) - Winther, Naja Stausholm; Holck, Emil Nielsen; Mogensen, Lone Juul Hune; Karim, Salma Raghad; Eftekhari, Ashkan; Christiansen, Evald Høj
Abstract: Objectives: The present study aimed to compare safety and long-term prognosis of patients with chronic total coronary occlusions (CTO) stratified for remaining CTOs after percutaneous coronary intervention (PCI). Design: The study cohort consisted of patients with coronary artery disease who underwent CTO PCI in a high volume tertiary center from 2009 to 2019 and were registered in Danish high-quality registers. Patients with successful PCI of all CTOs were compared to patients with ≥1 remaining CTO post-procedural. Primary endpoints were analysed using Cox-regression and Kaplan-Meier estimates, and included all-cause mortality, major adverse cardio- and cerebrovascular events (MACCE) and a 30-day safety endpoint. Results: Procedural success rate was 87.7%, and 76.5% of patients had all CTO(s) opened post-PCI. Safety endpoint occurred in 4.6% of patients, and more frequently in patients with remaining CTO(s) (RD 4.9, 95%CI 0.1, 9.8). All-cause mortality was higher in patients with remaining CTO(s) (Unadjusted HR 1.65, 95% CI 1.03, 2.47, p = .015. Adjusted HR 1.32, 95%CI 0.88–1.99, p = .18) after eight years of follow-up. Risk of MACCE was significantly higher in patients with remaining CTO(s) (Unadjusted HR 1.79, 95% CI 1.34–2.41, p < .001. Adjusted HR 1.51, 95% CI 1.11–2.05, p = .009). Conclusions: In our centre, CTO PCI was associated with high success rate and low risk of 30-days complications. Presence of remaining CTO(s) after final revascularization attempt was associated with higher but statistically insignificant long-term mortality but was an independent predictor of MACCE.